2017
DOI: 10.12998/wjcc.v5.i5.178
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor therapy and atrioventricular block: Do we need to worry?

Abstract: Ticagrelor is a potent, direct P2Y12 antagonist with rapid onset of action and intense platelet inhibition, indicated in patients with acute coronary syndromes (ACS). This drug is usually well tolerated, but some patients experience serious adverse effects: Major bleeding; gastrointestinal disturbances; dyspnoea; ventricular pauses > 3 s. Given the unexpected high incidence of bradyarrhythmias, a PLATO substudy monitored this side effect, showing that ticagrelor was associated with an increase in the rate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Few reports of clinically significant ticagrelor-related bradycardia requiring drug discontinuation have been published. 8 To the best of our knowledge, we report the first case of severe sinus respiratory arrhythmia combined with AV block after ticagrelor loading. Cheyne-Stokes respiration frequently occurs in patients with congestive heart failure 9 and has been associated with exaggerated respiratory heart rate variations.…”
Section: Discussionmentioning
confidence: 85%
“…Few reports of clinically significant ticagrelor-related bradycardia requiring drug discontinuation have been published. 8 To the best of our knowledge, we report the first case of severe sinus respiratory arrhythmia combined with AV block after ticagrelor loading. Cheyne-Stokes respiration frequently occurs in patients with congestive heart failure 9 and has been associated with exaggerated respiratory heart rate variations.…”
Section: Discussionmentioning
confidence: 85%
“…The conduction abnormalities induced are often asymptomatic without the need for a permanent pacemaker [ 1 ]. The abnormalities are sometimes even transient and resolve with discontinuation of ticagrelor [ 7 ]. However, a minority of patients did require pacemaker placement due to persistent sinoatrial disease, like the patient reported here [ 8 ]; however, unlike our patient, most of the patients requiring a pacemaker had some underlying conduction abnormality [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ticagrelor a potent P2Y12 inhibitor is recommended as first-line antithrombotic agent in addition to Aspirin in acute coronary syndrome; however, it may exert a deleterious effect in patients already presenting with symptomatic bradycardia causing atrioventricular block published in few case reports. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%